Cryopreservation of Multicellular Spheroids Derived from Primary Culture of Newborn Piglet Spinal Ganglion Cells - Ali, Sabina G.; Bozhok, Galina A. (Problems of Cryobiology and Cryomedicine, 2019)
Dorsal root ganglia (DRG) are a potential source of neural stem cells, since they contain the neural crest-derived cells capable to diï¬€erentiate into neurons and diï¬€erent subpopulations of glial cells. It is known that under certain culture conditions, the DRG cells, derived from neonatal piglets form the ï¬‚oating multicellular spheroids (MSs), capable to produce the ï¬broblast-like cells (FLCs), glial cells (GCs) and neuron-like cells (NLCs). Here, we have cryopreserved the MSc, derived under serum-free culture conditions using 5, 7.5, 10% dimethyl sulfoxide (DMSO) and two-stage regimen of freezing. After cryopreservation, the MSs were established to preserve the capability to adhere as well as to produce three cell types: FLCs, GCs and NLCs. However, the capability of frozen-thawed MSs to produce diï¬€erent cell types was reduced. The cryoprotectant concentration aï¬€ected the cell type, prevailing in the culture, derived from the frozen-thawed MSs. After cryopresevation with 10% DMSO, the monolayer consisted mainly of FLCs, while with 5 and 7.5% DMSO it mostly comprised GLCs. Â Probl Cryobiol Cryomed 2019; 29(4):Â 354-364